DIGITAL THEOLOGY IN PRACTICE: TRANSFORMING THEOLOGICAL EDUCATION THROUGH VIRTUAL LEARNING ECOSYSTEMS - Ni Made Anggreni (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The rapid development of digital technologies has significantly reshaped theological education worldwide. This study explores how Digital Theology emerges as both a field of inquiry and a pedagogical practice within virtual learning ecosystems. Through the integration of Learning Management Systems, interactive video platforms, online libraries, and AI-assisted tools, theological education expands beyond traditional classroom boundaries. This transformation not only enhances accessibility and flexibility but also redefines how students engage with sacred texts, spiritual formation, and critical theological reflection. Using qualitative analysis and case-based observations, this paper argues that virtual learning ecosystems foster collaborative, reflective, and contextually responsive theological learning. Ultimately, Digital Theology offers a new paradigm that harmonizes technological innovation with the spiritual and ethical foundations of theological education.